Spreading of X chromosome inactivation via a hierarchy of defined Polycomb stations - Pinter, Stefan F. (Cold Spring Harbor Laboratory Press, 2012)
X chromosome inactivation (XCI) achieves dosage balance in mammals by repressing one of two X chromosomes in females. During XCI, the long noncoding Xist RNA and Polycomb proteins spread along the inactive X (Xi) to initiate chromosome-wide silencing. Although inactivation is known to commence at the X-inactivation center (Xic), how it propagates remains unknown. Here, we examine allele-specific binding of Polycomb repressive complex 2 (PRC2) and chromatin composition during XCI and generate a chromosome-wide profile of Xi and Xa (active X) at nucleosome-resolution. Initially, Polycomb proteins are localized to ∼150 strong sites along the X and concentrated predominantly within bivalent domains coinciding with CpG islands (“canonical sites”). As XCI proceeds, ∼4000 noncanonical sites are recruited, most of which are intergenic, nonbivalent, and lack CpG islands. Polycomb sites are depleted of LINE repeats but enriched for SINEs and simple repeats. Noncanonical sites cluster around the ∼150 strong sites, and their H3K27me3 levels reflect a graded concentration originating from strong sites. This suggests that PRC2 and H3K27 methylation spread along a gradient unique to XCI. We propose that XCI is governed by a hierarchy of defined Polycomb stations that spread H3K27 methylation in cis.